Implementation of fire incident response time service policy in Manado City Fire Service - Palendeng, Raymond Stefanus; Kairupan, Sisca Beatrix; Bulo, Laurens (Technium Social Sciences Journal, 2024)
The purpose of the research is to find out, analyze and describe the Implementation of Response Time Service Policy for Fire Incident Management in Manado City Fire Service and the determinant factors. The method used in this research is qualitative research method. The results showed that in the implementation of the Fire Event Response Time Service Policy in Manado City Fire Service, there are six important indicators, namely (1) Media call center which plays an important role in fire handling as the main link between the community and fire handling officials, (2) Implementing apparatus consisting of various roles with complementary responsibilities, from fire fighting to fire prevention, (3) Fire fighting facilities in this case facilities and infrastructure which are important elements in fire management efforts, (4) The situation of the fire location which greatly affects the response and fire management activities, (5) The distance and limitations of hydrants which affect the speed and effectiveness of fire management, and (6) Coordination between agencies in fire management plays an important role in ensuring a fast, effective, and coordinated response to fire situations. The determinant factor in fire incident management efforts is Human Resources (HR) which is the main driving factor in the implementation of fire management. The Human Resources referred to here are the number of fire fighting personnel. Next is the facilities or facilities and infrastructure supporting firefighting activities which include vehicles and other extinguishing aids used in extinguishing activities, then the limited budget both in terms of the budget for operations and the budget for procurement and repair of facilities and infrastructure supporting extinguishing activities.